Partial Budgeting of the Application of Teat-dipping to Control Mastitis in Small Farms - Dikky Indrawan; Etih Sudarnika; Chaerul Basri; Abdul Zahid Ilyas; Nyayu Lathifah Tirdasari; Mirnawati Sudarwanto (Acta VETERINARIA Indonesiana, 2019)
Subclinical mastitis has a higher prevalence than clinical mastitis in many small farmers in Bogor city, and it could reach more than 80 percent. However, the application of teat-dipping could help small farms to control subclinical mastitis prevalence. The objective of this study was to measure the cost of teat-dipping application as subclinical mastitis control in small dairy farms. The partial budget was employed based on the experimental data collected in small dairy farms in Bogor. A number of cows were the basis of simulation for the mean of milk value and the application cost. The findings show an incentive for farmers to apply teat dipping in their farms. The incentive of teat dipping application could be improved to prevent sub-clinical mastitis infection and increase milk production.